Enhancing Financial Resilliance: a Study of Financial Ratios to Predict Financial Distress in Indonesian Life Insurance Firms During Covid-19 Era - Diva Syachrani Sugandi; Evi Gantyowati (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
The Covid-19 phenomenon and a series of insurance default events increase the risk of bankruptcy. Financial distress analysis becomes a crucial study to prevent bankruptcy. This research was conducted to present empirical evidence of the influence of premium growth ratio, liquidity ratio, risk-based capital, investment adequacy ratio, technical reserve growth ratio, and investment income ratio against financial distress prediction in life insurance companies listed on the Indonesian Insurance Directory for the years 2019-2021. The study employed a quantitative approach with logistic regression and 120 observation samples. The conclusions drawn from this research indicate that the premium growth ratio, liquidity ratio, and risk-based capital significantly have a negative impact on the prediction of financial distress, whereas the investment adequacy ratio and growth of technical reserves ratio have a positive impact. However, this research could not provide empirical evidence of the influence investment income in predicting financial distress. The results of this study contribute to insurance companies in managing their financial health by identifying risk factors based on financial ratios and taking appropriate preventive measures. Stakeholders can also enhance supervision on financial health indicators and consider establishing limits for the investment adequacy ratio to maintain stability in the insurance industry. Keywords: bankruptcy, Covid-19, financial distress, financial health ratio, insurance